Pengaruh Public Service Motivation Terhadap Job Satisfaction dan Organizational Citizenship Behavior pada Pegawai Badan Pusat Statistik - Widyananda, Ardadi; Emilisa, Netania; Pratana, Raditya (Jurnal Ekonomi : Journal of Economic, 2014)
AbstractThis purpose of research is to identify the influence of public service motivation on job satisfaction and organizational citizenship behavior on employees of Statistics Indonesia. The methods of analysis used in this research is a simple regression analysis were processed with SPSS software version 13.0. Collecting data in this research are based on a sample of 59 employees Bureau of Finance and Directorate of Statistical Dissemination in Statistics Indonesia. In this research, the authors investigated the influence of public service motivation on job satisfaction and organizational citizenship behavior on employees of Statistics Indonesia. Based on the analysis results and discussion can be concluded that public service motivation have a significant influence on job satisfaction and organizational citizenship behavior on employees of Statistics Indonesia.Keywords: public service motivation, job satisfaction, organizational citizenship behavior